The Core of the Respiratory Syncytial Virus Fusion Protein Is a Trimeric Coiled Coil - Matthews, Jacqueline M. (American Society for Microbiology, 2000)
Entry into the host cell by enveloped viruses is mediated by fusion (F) or transmembrane glycoproteins. Many of these proteins share a fold comprising a trimer of antiparallel coiled-coil heterodimers, where the heterodimers are formed by two discontinuous heptad repeat motifs within the proteolytically processed chain. The F protein of human respiratory syncytial virus (RSV; the major cause of lower respiratory tract infections in infants) contains two corresponding regions that are predicted to form coiled coils (HR1 and HR2), together with a third predicted heptad repeat (HR3) located in a nonhomologous position. In order to probe the structures of these three domains and ascertain the nature of the interactions between them, we have studied the isolated HR1, HR2, and HR3 domains of RSV F by using a range of biophysical techniques, including circular dichroism, nuclear magnetic resonance spectroscopy, and sedimentation equilibrium. HR1 forms a symmetrical, trimeric coiled coil in solution (K(3) ≈ 2.2 × 10(11) M(−2)) which interacts with HR2 to form a 3:3 hexamer. The HR1-HR2 interaction domains have been mapped using limited proteolysis, reversed-phase high-performance liquid chromatography, and electrospray-mass spectrometry. HR2 in isolation exists as a largely unstructured monomer, although it exhibits a tendency to form aggregates with β-sheet-like characteristics. Only a small increase in α-helical content was observed upon the formation of the hexamer. This suggests that the RSV F glycoprotein contains a domain that closely resembles the core structure of the simian parainfluenza virus 5 fusion protein (K. A. Baker, R. E. Dutch, R. A. Lamb, and T. S. Jardetzky, Mol. Cell 3:309–319, 1999). Finally, HR3 forms weak α-helical homodimers that do not appear to interact with HR1, HR2, or the HR1-HR2 complex. The results of these studies support the idea that viral fusion proteins have a common core architecture.